Palladium nanoparticle-decorated reduced graphene oxide sheets synthesized using Ficus carica fruit extract: A catalyst for Suzuki cross-coupling reactions - Anasdass, Jaculin Raiza; Kannaiyan, Pandian; Raghavachary, Raghunathan; Gopinath, Subash Chandra Bose; Chen, Yeng (Public Library of Science, 2018)
We present a biogenic method for the synthesis of palladium nanoparticle (PdNP)-modified by reducing graphene oxide sheets (rGO) in a one-pot strategy using Ficus carica fruit juice as the reducing agent. The synthesized material was well characterized by morphological and structural analyses, including, Ultraviolet-Visible spectroscopy (UV-Vis), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and Transmission Electron Microscopy (TEM) and Raman spectroscopy. The results revealed that the PdNP modified GO are spherical in shape and estimated to be a dimension of ~0.16 nm. The PdNP/graphene exhibits a great catalytic activity in Suzuki cross-coupling reactions for the synthesis of biaryl compounds with various substrates under both aqueous and aerobic conditions. The catalyst can be recovered easily and is suitable for repeated use because it retains its original catalytic activity. The PdNP/rGO catalyst synthesized by an eco-friendly protocol was used for the Suzuki coupling reactions. The method offers a mild and effective substitute to the existing methods and may significantly contribute to green chemistry.